Exploring the Nexus Between Working Benefits and Company Characteristics in Creative Industries - Micak Peter (Folia Oeconomica Stetinensia)
Creative industries nowadays stand as one of the driving forces behind modern knowledge-based economies. Despite their many advantages, this research focuses on some of the less positive aspects of their development, notably less than optimal working conditions.